δ44/40Ca, Mg/Ca and δ18O ratios of planktonic foraminifera from the Nordic Seas - Kozdon, Reinhard (2007)
A new approach for a solid delta44/40Ca temperature calibration of the polar to subpolar planktonic foraminifera N. pachyderma (sin.) is presented, based on a broad sample pool comprising North and South Atlantic genotyped net catches and Nordic Seas core top sample material. With this new additional SST proxy, the 'cold end' error of proxy temperature calibrations was addressed in combining delta44/40Ca, Mg/Ca and delta18O ratios in tests of N. pachyderma (sin.). At water temperatures below about 3.5°C, the proxy to temperature relationship recorded in the Mg/Ca and delta44/40Ca signal simultaneously disappears. Based on these ‘cold-end‘ proxy-data we present a model demonstrating that the aberrant delta44/40Ca and Mg/Ca ratios in N. pachyderma (sin.) calcified in cold polar waters can be interpreted by a two-step chemical modification of vacuolized seawater during its cytosolar transport to the calcification site.